Study of the Technology of Production of Sausage Products Based on Food Additives (Texas Journal of Multidisciplinary Studies, 2022)
the use of starter cultures as a factor in the formation of the quality of sausages has been studied; selected and substantiated doses of starter added to sausage mince; the change in the content of free amino acids in minced meat during sedimentation was studied; the influence of plant additives from pumpkin seeds on the properties of model mince systems was studied; the technology of production of boiled-smoked sausages with the use of starter cultures and food additives is given.